NEGOTIATING PIETY: Locality, Identity, and Contestation within Tablighi Jamaat in Southeast Asia - Sofiandi, Sofiandi; Nuh, Zulkifli M; Masbukin, Masbukin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This article explores the internal dynamics of the Tablighi Jamaat in Southeast Asia through an anthropological approach to religion. As a transnational da'wah movement originating from colonial India, the Tablighi Jamaat promotes a particular form of piety that interacts with, is negotiated, and at times contested within the local socio-cultural contexts of Indonesia and Malaysia. Drawing on the theories of locality (Appadurai), piety as a social construct (Asad & Mahmood), and symbolic capital (Bourdieu), the article highlights how language, travel experiences (safar), ethnicity, and gender serve as key arenas in the formation of hierarchy and authority within the movement. Through a critical reading of language adaptation, cultural resistance, and shifts in proselytizing practices by youth and converts, this study argues that piety within the Tablighi Jamaat is not a fixed entity, but rather the result of ongoing negotiations between global values and local realities. These findings contribute to a deeper understanding of transnational Islam as a project shaped by locality, conflict, and social transformation.